Chief Executive Officer Inside Debt Holdings and Labor Investment Efficiency1. (28th August 2019) - Mo, Kyoungwon; Kim, Young Jin; Park, Kyung Jin
Abstract: We show how chief executive officer (CEO) inside debt holdings affect corporations' labor investment behavior. We empirically find a positive association between CEO inside debt holdings shown to increase their conservatism and long‐term horizons due to deferred payments and labor investment efficiency recognized as an integral factor in a firm's long‐term survival and growth. Additional analyses reveal that CEO inside debt holdings lead to a greater tendency to reduce net hiring amid excess labor availability than is observed when levels are optimal. This tendency is especially marked when CEO power is strong and when the firm has relatively high financial liquidity and leverage.